Examination of the determinants of credit constraints in the rural agricultural credit market of Nigeria - Kofarmata, Yusuf Ibrahim; Applanaidu, Shri Dewi; Hassan, Sallahuddin (2015)
Improving and sustaining production efficiency of small farmers under the dominance of borrowing constraints require the improvement of access to credit among other factors of production.Although there has been a substantial literature on credit rationing in developing world, there is surprisingly little information on the characteristics of farmers who are likely to be affected by the factors identified to be the credit constraints.Therefore, using data of 171 respondents from the household survey, the research provides new evidence on credit rationing and borrowing constraints for rural farmers in Nigeria.The estimates of the logistic regression model reveals that constraints to credit is negatively related to educational attainments of the farmers and positively correlated with high off-farming business.Based on the findings, the study recommends the need for the policy makers to strengthen the lending capacity of rural credit markets, redesign the educational system and encourage micro businesses in the rural areas.